ONSPRIDE: An Ontology-based Framework for Privacy by Design in Distributed Networks Apps - da Silva, Marco Antonio Colombo; Nakamura, Luis Hideo Vasconcelos; Filho, Geraldo P. Rocha; Veiga, Luís; Meneguette, Rodolfo Ipolito (Journal of Internet Services and Applications, 2025)
With the advancement of technologies for data registration in distributed networks, the concern of users and developers of computerized solutions with the privacy of sensitive data has increased. Thus, this work addresses a conceptual solution for an ontology-based framework so that any entity willing to provide a service using Distributed Ledger Technology (DLT) networks can model the set of privacy attributes of its system according to the business rules of its service. The solution proposed in this work encompasses the development of an architecture aimed at providing computational support for the privacy design of the actors involved in the offering and consumption of services implemented in DLTs. The architecture also includes a framework called ONSPRIDE, which uses previously stored domain ontologies to translate business rules into requirements and privacy. We conducted a proof of context by comparing the performance of two Hyperledger Fabric networks. For this purpose, we conducted a controlled experiment in which both networks operate a smart contract that manages attendance records for outdoor events. The main difference between the networks is that one uses a Certificate Authority (CA) to issue access certificates, while the other issues certificates manually. We compared the results obtained through the reports generated by the Hyperledger Caliper tool. In addition, the performance of the initialization and connection of agents in a Self-Sovereign Identity system was measured. The results of this study provide valuable insight that can help developers choose the most suitable ledger type for their Hyperledger projects and support decision-making regarding adopting a Self-Sovereign Identity system.